Bill T. Jones dancing to the promised land / Arnie Zane Dance Co. - Jones, Bill T. (Dance series., 2004)
Bill T. Jones is one of the most powerful forces in modern dance. His dances are completely unique, provocative and contemporary. Take a look at his life, work and creative process in this award-winning film.